PERTANGGUNG JAWABAN PIDANA TERHADAP NOTARIS YANG MELAKUKAN TINDAK PIDANA DIKARENAKAN KELALAIAN NOTARIS PPAT DALAM MEMBAYARKAN PAJAK. (STUDI KASUS PUTUSAN NOMOR: 300 /PID.B/2015/PN.DPS) - Maulana Yusuf; Siti Hajati Hoesin (The Juris, 2021)
The obligation to pay Land and Building Rights Acquisition Fee (BPHTB) is in principle the obligation of the taxpayer and not the obligation of the Notary/PPAT. Notary/PPAT only helps its clients to deposit BPHTB taxes. Notary/PPAT only tries to provide the best service for its clients, or in other words, Notary/PPAT only accepts BPHTB tax payments. The problem in this research is: How is the Notary/PPAT’s obligation in paying BPHTB that has been entrusted to him in relation to the transfer of rights through buying and selling. This research is a normative study, the data used to answer this problem is secondary data. To obtain secondary data, library research is needed. The theory used in this research is the theory of responsibility and the theory of justice. The results of the research conclude that the Notarys/PPAT Tanah is obliged to pay BPHTB taxes that have been entrusted to him, even though in reality it is not regulated in the prevailing laws and regulations. Notary/PPATs that do not make BPHTB tax payments that have been deposited with them will have legal consequences. Notary/PPAT in this case has responsibility for its obligations in paying BPHTB, but in reality Notary/PPAT does not pay BPHTB to the State Treasury or to the Regional Treasury. The analysis studied in the research decision Number 300 / Pid.B / 2015 / PN.Dps. It is correct that the panel of judges sentenced the defendant based on the statements of the parties and the witnesses as well as the evidence in the trial. So in this case the defendant was charged under Article 372 of the Criminal Code which is an Article of embezzlement. The Panel of Judges determined according to the elements and offenses the defendant had committed.